Pengaruh Kompetensi Sumber Daya Manusia dan Tingkat Religiusitas terhadap Kualitas Laporan Keuangan dengan SPIP sebagai Variabel Intervening - M. Fahrur Rozi; Sugih Sutrisno Putra; Yeti Apriliawati (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aims to determine the effect of human resource competence, the use of information technology, and the level of religiosity on the quality of financial reports with the government's internal control system (SPIP) as an intervening variable in the Local Government Agencies of Bandung City. The research method that used in this research is quantitative method. The population in this study is the Local Government Agencies of Bandung City with a sample of 26 Departments and Agencies under the Bandung City government. The data analysis method that used in this research is path analysis with the help of the SPSS application. The results showed that the competence of human resources and the level of religiosity had a positive and significant effect on the quality of financial reports either partially or simultaneously, as well as directly or indirectly through government internal control systems (SPIP).